Lady Hotspur - Gratton, Tessa (Gratton, Tessa. Queens of Innis Lear., 2020)
"STRIKE FAST, LOVE HARD, LIVE FOREVER This is the motto of the Lady Knights--sworn to fealty under a struggling kingdom, promised to defend the prospective heir, Banna Mora. But when a fearsome rebellion overthrows the throne, Mora is faced with an agonizing choice: give up everything she's been raised to love, and allow a king-killer to be rewarded--or retake the throne, and take up arms against the newest heir, Hal Bolingbrooke, Mora's own childhood best friend and sworn head of the Lady Knights. Hal loathes being a Prince and is mired in guilt and regrets, drinking away every night instead on the Throne of Misrule. She yearns to live up to the wishes of those she loves best--but that means sacrificing her own heart, and so Hall would rather disappoint everyone until the moment she can rise to prove those expectations wrong. And between these two fierce Princes is the woman who will decide all their fates: Lady Isarna Hotspur, the passionate and bold knight whose support will turn the tides of the coming war--or bring their kingdom to its ruin"--